Perangkap Hama untuk Arsip di Kantor Unit Pengelola Kegiatan (UPK) Kecamatan Koto IX Tarusan - Zonicha, Sonya; Ardoni, Ardoni (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2017)
The purpose of this paper is to explain the process of making the trap pests in the maintenance of the archive against the head and members of the Office Unit Manager (UPK) Activity Sub Koto XI Tarusan. The creation of this pest trap aimed at keeping the archives from damage caused by insects.The method used is descriptive method. Data collected through direct research, based on the facts that happened on the field Unit Office Manager (UPK) Activity Sub Koto XI Tarusan. Observations were made during 10 days.Based on the results of the study it was concluded that to prevent insects breeding there is no longer carried out fumigation, simply by mounting the trap pests in archives. The materials and tools used in pembutan this pest trap is a simple tool and material. This is because there are a lot of advantages derived from the making of this pest traps, traps the pest has no effect against damage to archives, and does not require special treatment because once created enough placed on shelves hung way archives that have been given a nail, a distance which is not far from the surface of the floor then the insects will go by itself.Keyword: Manufacture Of Trap Pests.